New Detrital Apatite Fission Track Thermochronological Constraints on the Meso-Cenozoic Tectono-Thermal Evolution of the Micangshan-Dabashan Tectonic Belt, Central China - Tian, Tao; Yang, Peng; Yao, Jianming; Duan, Zhonghui; Ren, Zhanli; Fu, Deliang; Yang, Fu (Frontiers in Earth Science, 2021)
The Micangshan-Dabashan tectonic belt, located in the southern Qinling-Dabie Orogen near the northeastern Tibetan Plateau, is a crucial area for understanding the processes and mechanisms of orogenesis. Previous studies have been focused on the cooling process via thermochronology and the mechanism and process of basement uplift have been investigated. However, the coupling process of basement exhumation and sedimentary cap cooling is unclear. The tectono-thermal history constrained by the detrital apatite fission track (AFT) results could provide valuable information for understanding crustal evolution and the coupling process. In this study, we provided new detrital AFT thermochronology results from the Micangshan-Dabashan tectonic belt and obtained nine high-quality tectono-thermal models revealing the Meso-Cenozoic cooling histories. The AFT ages and lengths suggest that the cooling events in the Micangshan area were gradual from north (N) to south (S) and different uplift occurred on both sides of Micangshan massif. The cooling in Dabashan tectonic zone was gradual from northeast (NS) to southwest (SW). The thermal histories show that a relatively rapid cooling since ca. 160 Ma occurred in the Micangshan-Dabashan tectonic belt, which was a response to the event of Qinling orogenic belt entered the intracontinental orogenic deformation. This cooling event may relate to the northeastward dextral compression of the Yangtze Block. The sedimentary cap of Cambriano-Ordovician strata responded positively to this rapid cooling event and entered the PAZ since ca. 63 Ma. The deep buried samples may be limited affected by climate and water erosion and the accelerated cooling was not obvious in the Late Cenozoic. Collectively, the cooling processes of basement and sedimentary cap in Micangshan-Dabashan tectonic belt were inconsistent. The uplift of the sedimentary area is not completely consistent with that of the basement under thrust and nappe action. The rigid basement was not always continuous and rapidly uplifted or mainly showed as lateral migration in a certain stage because of the different intensities and modes of thrust and nappe action, and the plastic sedimentary strata rapidly uplifted due to intense folding deformation.